Визначення токсичності водних зразків з використанням гематологічних параметрів риб - Верголяс, М.Р. (Фактори експериментальної еволюції організмів, 2015)
Aims. Developing effective methods for evaluation due to anthropogenic changes of aquatic ecosystems. Methods.
Using cyto- and genotoxic methods for evaluating the quality of the water environment using test organisms fish, namely
their blood cells. Results. The investigated samples of water obtained before and aftertreatment of nitrate with the use
cytogenetic approaches have been shown changes in blood leukocyte formula fish Danio rerio (L.), and genetic changes
by micronucleus test of blood cells – red blood cells. Conclusions. This method is short term, yet technically simple,
versatile and important bioassays. Hematological parameters – definition of blood counts and micronucleus test in addition
to the standardized methods can be used for an objective and comprehensive assessment of toxic pollutants.
Keywords: hematological parameter, biotesting, cytotoxicity, water.